Strengthening the United Nations through deepened cooperation with NGOs, the private sector, and parliaments - Thomas Fues (Deutsches Institut für Entwicklungspolitik (DIE), 2005)
Serious deficits have until today prevented the United Nations (UN) from assuming the leadership role set out for it in the Charter in coming to terms with global challenges. The international debate over how this situation could be changed is more lively and concrete than ever before. One question involved in the debate is what contributions nongovernmental organizations (NGOs), the private sector, and parliaments can and should provide. The answers given tend to be controversial. The vision of the so-called Cardoso Commission, which would like to see the UN further developed into a world forum open to all actors, points in the right direction, though, at least for the time being, it has no real prospects of implementation. Instead, member states should, in a first step, act on the pragmatic proposals advanced by UN Secretary-General Kofi Annan. The long-term concern is to put in place two innovative structural elements: a consultative parliamentary assembly and a platform for global policy networks. This would in no way affect the primary responsibility of governments for the world organization. German politicians and NGOs should seek to become more involved in the UN process and support concrete progress, but without losing sight of the long-term reform perspective.
Keywords: 330